Black Patients with Acute Myocardial Infarction Experience Higher Mortality During Moderate to Long Hours of Emergency Department Crowding - Hsia, Renee Y. (Health Aff (Millwood), 2017)
This study investigated whether emergency department (ED) crowding affects blacks more than their white counterparts and the mechanisms behind which this might occur. Using a non-public database of patients with acute myocardial infarction (AMI) between 2001–2011 and hospital-level diversion data, we found that hospitals treating a high share of black AMI patients were more likely to experience ambulance diversion and that black patients fared worse compared to white patients experiencing the same level of ED crowding as measured by ambulance diversion. The 90-day and 1-year mortality rates among blacks exposed to high diversion levels were 2.88 (95% CI 0.64–5.12) and 3.09 (95% CI 0.31–5.88) percentage points higher, respectively, relative to whites, representing a relative increase of 19% and 14% for 90-day and 1-year death, respectively. Interventions that decrease the need for diversion in hospitals serving a high volume of blacks could potentially reduce these disparities.